Studying signal compartmentation in adult cardiomyocytes - Judina, Aleksandra; Gorelik, Julia; Wright, Peter T (Biochemical Society transactions, 2020)
Multiple intra-cellular signalling pathways rely on calcium and 3'-5' cyclic adenosine monophosphate (cAMP) to act as secondary messengers. This is especially true in cardiomyocytes which act as the force-producing units of the cardiac muscle and are required to react rapidly to environmental stimuli. The specificity of functional responses within cardiomyocytes and other cell types is produced by the organellar compartmentation of both calcium and cAMP. In this review, we assess the role of molecular localisation and relative contribution of active and passive processes in producing compartmentation. Active processes comprise the creation and destruction of signals, whereas passive processes comprise the release or sequestration of signals. Cardiomyocytes display a highly articulated membrane structure which displays significant cell-to-cell variability. Special attention is paid to the way in which cell membrane caveolae and the transverse-axial tubule system allow molecular localisation. We explore the effects of cell maturation, pathology and regional differences in the organisation of these processes. The subject of signal compartmentation has had a significant amount of attention within the cardiovascular field and has undergone a revolution over the past two decades. Advances in the area have been driven by molecular imaging using fluorescent dyes and genetically encoded constructs based upon fluorescent proteins. We also explore the use of scanning probe microscopy in the area. These techniques allow the analysis of molecular compartmentation within specific organellar compartments which gives researchers an entirely new perspective.